Dilema Restorative Justice Kewenangan Dalam Penegakan Hukum - Amin, Muhammad Nur; Sugianto, Bambang (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2025)
The purpose of this study is to provide an overview of how to execute the minutes of the peace agreement in restorative justice and what products are appropriate in the use of the term restorative justice. The analytical method used in this study is a normative juridical research method. The results of the study concluded that the minutes of the peace agreement issued by the police and the prosecutor's office in restorative justice cannot be executed because the product issued is not a determination but an agreement report, therefore the minutes of the agreement have executive rights if it has been registered or notified to the court and has been obtain a determination, so that the right legal product in the use of the term restorative justice is in the form of a determination without reducing the meaning of the minutes of the peace agreement made by the parties.